Influence of the hydrophobic domain on the self-assembly and hydrogen bonding of hydroxy-amphiphiles. Issue 21 (17th May 2019) - Andrushchenko, Valery; Pohle, Walter
Abstract : IR spectroscopy paired with calculations reveals that structurally similar amphiphiles ODA and DOG form very different supramolecular assemblies. Abstract : The amphiphiles 1-octadecanol (octadecyl (stearyl) alcohol, ODA) and 1, 2-dioleoylglycerol (DOG) were studied by IR spectroscopy and X-ray diffraction combined with multiscale theoretical modeling. The computations allowed us to rationalize the experimental findings and deduce the supramolecular structure of the formed assemblies while providing a fairly detailed insight into their hydrogen-bonding patterns. IR spectra revealed that the amphiphilic assemblies dramatically differ in structural order and hydrogen-bond strength, both being high in ODA and low in DOG. On the other hand, both compounds demonstrated common features, namely a splitting of the IR bands arising from O–H stretching vibrations ( ν OH) as well as complete hydrophobicity. However, the observed phenomena have different origins in the two amphiphiles. While the ν OH split in ODA occurs due to a vibrational coupling along the string of inter-layer O–H⋯O hydrogen bonds, in DOG it arises from different types of hydrogen bonds (intra- and intermolecular). The hydrophobicity of ODA stems from the very tight O–H⋯O hydrogen bonding network connecting the opposite monolayers in a densely packed tilted crystalline phase (Lc ′), whereas in DOG it occurs because the polar sites are locked inside reverted micellar-like assemblies. ODA and DOG illustrate that, in the assemblies of amphiphilic hydroxyl compounds, hydrogen bonds can be formed in a wide structural latitude, which is primarily governed by the chemical nature of apolar chains. Such a wide structural variability of OH-involving hydrogen bonds can be essential for the biological functioning of relevant molecules, such as glycolipids, acylglycerols, and, potentially, glycoproteins and carbohydrates.